2004
DOI: 10.1081/cbi-200025991
|View full text |Cite
|
Sign up to set email alerts
|

Daily Increments of Light Hours Near Vernal Equinox Synchronize Circannual Testicular Cycle of Tropical Spotted Munia

Abstract: In some long-lived organisms, particularly in tropical birds and migrants that spend part of the year close to the equator, endogenous circannual rhythms have been demonstrated in seasonal events like reproduction, molt, and migration. These, like the circadian rhythms, are expressed only in constant conditions of illumination with a periodicity deviating from 1 yr. If birds followed this periodicity, they would soon be out of phase with the annual calendar and perish and, therefore, they would need to be sync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In other cases the reproductive activity is spread out over weeks or months, but nonetheless is clearly seasonal rather than continuous (e.g., most temperate-zone species ;Fitch 1970, Abts 1988, Aichinger 1992, Bauer 1992b, Alkins-Koo 2000. Proximate factors generally have proved more amenable to study, with robust evidence that seasonal reproduction can be initiated by stimuli such as variations in day length (Murton and Westwood 1977, Burns 1985, Kumar and Kumar 1991, Chandola-Saklani et al 2004, temperature (Obbard andBrooks 1987, Hart 2004), rainfall (Patterson Manuscript Lampo and Medialdea 1996, Madsen and Shine 1999b, Christian et al 2003, and food supply (Tinney et al 2001, Clouet 2003, Rubenstein and Wikelski 2003, or interactions between these factors (Janzen 1967, Johannes 1978, Kramer 1978, Garrido et al 2000, Hau 2001, Pankhurst and Porter 2003. Because the time of year at which reproduction occurs is a major axis of life-history variation, extensive research has sought to clarify both the proximate and ultimate reasons for the observed diversity in patterns of reproductive timing.…”
Section: Introductionmentioning
confidence: 99%
“…In other cases the reproductive activity is spread out over weeks or months, but nonetheless is clearly seasonal rather than continuous (e.g., most temperate-zone species ;Fitch 1970, Abts 1988, Aichinger 1992, Bauer 1992b, Alkins-Koo 2000. Proximate factors generally have proved more amenable to study, with robust evidence that seasonal reproduction can be initiated by stimuli such as variations in day length (Murton and Westwood 1977, Burns 1985, Kumar and Kumar 1991, Chandola-Saklani et al 2004, temperature (Obbard andBrooks 1987, Hart 2004), rainfall (Patterson Manuscript Lampo and Medialdea 1996, Madsen and Shine 1999b, Christian et al 2003, and food supply (Tinney et al 2001, Clouet 2003, Rubenstein and Wikelski 2003, or interactions between these factors (Janzen 1967, Johannes 1978, Kramer 1978, Garrido et al 2000, Hau 2001, Pankhurst and Porter 2003. Because the time of year at which reproduction occurs is a major axis of life-history variation, extensive research has sought to clarify both the proximate and ultimate reasons for the observed diversity in patterns of reproductive timing.…”
Section: Introductionmentioning
confidence: 99%
“…continuous darkness (Chandola et al, 1975). However, it may still use light in the synchronization of its annual gonadal cycle, as shown by the effects of small increments of 1.5-2 min daily light periods during the time around the vernal equinox (Chandola-Saklani et al, 2004). Spotted munia have been reported to show both circadian and circannual rhythms (Bhatt and Chandola, 1985;Pant and Chandola-Saklani, 1992;Budki et al, 2012) (P.D., S.M., S.R.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, photoperiodic change entrains certain stages of an annual cycle, and particularly gonadal growth and regression (Gwinner , Chandola‐Saklani et al . , Dawson 2008a), and the rates of the physiological processes usually correlate with the rate of change in day length (Chandola‐Saklani et al . , Dawson 2008a).…”
Section: Discussionmentioning
confidence: 99%